The impact of COVID-19 pandemic on head and neck cancer diagnosis and treatment - Nao Yamamoto Nishimura; Kengo Aoki; Shihoko Koyama; Minako Nishio; Tomoyuki Otsuka; Masayoshi Miyazaki; Tadashi Yoshii; Shinji Otozai; Junji Miyabe; Mizuki Korematsu; Takashi Fujii; Miki Ishibashi (Elsevier, 2024)
Background/purpose: Following the COVID-19 pandemic, there were reports of diagnostic delays and a surge in the prevalence of advanced head and neck cancer (HNC). We conducted a retrospective study on the impact of COVID-19 on the number of newly diagnosed HNC among patients who underwent screening at our center to understand the temporal changes. Materials and methods: We investigated the Union for International Cancer Control guidelines-TNM classification, presence of subjective symptoms at the time of consultation, and initial treatment from the medical records of first-time patients with HNC who visited our head and neck surgery department during 2019-2021 and compared them with those before (2019) and after (2020-2021) the pandemic. Results: A total of 1245 patients were included in the study. The number of patients were 437, 417, and 391 in 2019, 2020, and 2021, respectively, indicating a downward trend following the pandemic. When the incidence of early (stage 0-II) and advanced (stage III-IV) HNC cancers was compared, the proportion of patients with early-stage cancer declined. Among them, significant primary tumor progression was observed in T classification. The number of patients with no subjective symptoms at initial diagnosis was decreasing significantly. Conclusion: A decrease in the proportion of HNC patients with early-stage cancer and primary tumor progression was observed after the pandemic in 2020 and 2021. The number of early-stage malignancies may have dropped due to patients' unwillingness to visit a doctor.